Ultrasound Diagnosed Disorders of Subacromial Shoulder Pain Patients: A Retrospective Study at a Tertiary Care Rural Hospital, Mewat, Haryana - Depinder Kaur; Harnam Madan; Surendra Kumar; Saurabh Anand; Manjeet Dhand (Journal of Clinical and Diagnostic Research, 2021)
Introduction: Shoulder pain is leading cause of disability and pain among musculoskeletal pain patients. Ultrasound is coming in a bigger way for diagnosis and management of subacromial pain due to its low cost, easy availability and accuracy in detecting soft tissues pathologies and for planning further treatment. Aim: To assess the role of diagnostic Ultrasound (US) in subacromial shoulder pathologies evaluation in shoulder pain patients. Materials and Methods: This was a retrospective observational study conducted on 98 patients who presented with subacromial shoulder pain. Diagnostic ultrasound examination was done and patients were categorised based upon underlying pathology and analysed in terms of frequency. Results: Most common ultrasound findings in subacromial shoulder pain patients were subacromial bursopathy 46 (46.93%) followed by Rotator cuff pathology including tear 38 (38.77%), mixed pathology 9 (9.18%) and Acromioclavicular (AC) joint pathology 5 (5.10%). Isolated biceps pathology was not seen in our study rather biceps pathology along with other tendon and joint involvement was observed. Conclusion: The findings in the present study imply that diagnostic ultrasound of shoulder pain patients helps to stratify them into different categories for better understanding of underlying pathology and targeted treatment approach. Ultrasound shall be used as an outpatient primary diagnostic modality for evaluation of subacromial shoulder pain patients.